1996
DOI: 10.1103/physrevb.53.4549
|View full text |Cite
|
Sign up to set email alerts
|

Resonant interaction of phonons with surface vibrational modes in a finite-size superlattice

Abstract: We study theoretically the interaction of phonons with surface vibrational modes in a finite-size superlattice with a free surface. A phonon incident normally on the superlattice from a substrate is perfectly reflected, i.e., the reflection rate is unity irrespective of frequency. However, it comes back to the substrate with a large time delay when the frequency coincides with an eigenfrequency of the surface mode. This result is attributable to the resonant interaction of incident phonons with a vibrational m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…͑23͒ is a necessary condition for the existence of surface-localized modes in the SL with a free surface. 5,14 These modes correspond to the Wallis modes of the semiinfinite one-dimensional chain with two atoms per unit cell. [15][16][17] It is well known that the Wallis mode appears when the atom at the end has smaller mass than the other atom.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…͑23͒ is a necessary condition for the existence of surface-localized modes in the SL with a free surface. 5,14 These modes correspond to the Wallis modes of the semiinfinite one-dimensional chain with two atoms per unit cell. [15][16][17] It is well known that the Wallis mode appears when the atom at the end has smaller mass than the other atom.…”
Section: Discussionmentioning
confidence: 99%
“…͑19͒ leads to ͉͉Ӷ1 or ϳ0, because ͉S(N)͉ ϭsinh N/sinh ϾN. In the previous work, 14 it is shown that the equation ϭ0 gives the eigenfrequency s of the surface localized mode. That is, there is the possibility that Tϳ1 is realized only for the frequency near s .…”
Section: շ␥ ͑20͒mentioning
confidence: 98%
See 2 more Smart Citations
“…The theoretical studies on the cavity phonons in SLs developed so far are mostly restricted to this case with k ʈ = 0. 22,23 For these nonpropagating local modes, three kinds of acoustic vibrations are treated to be decoupled from each other ͑valid in the isotropic approximation, for example͒ and accordingly the mathematical analysis is rather straightforward.…”
Section: Introductionmentioning
confidence: 99%